Moringa oleifera seed derivatives as natural bio-coagulants in water treatment process - Aziz Zaid, Aziz Qannaf (2020)
River water in many parts of the world used for drinking purpose after some treatments. Consequently, the turbidity in untreated water is often conventionally removed by treating the water with expensive chemicals, many of which are not environmentally friendly. In fact, using chemicals materials in water treatments have some negative effects to human health. Therefore, there is a need to use some natural materials as an alternative to replace chemicals. Moringa oleifera is an important commodity plants which has been used for the treatment of water in tropical part of the world. In this study, the potential of Moringa oleifera seeds as bio-coagulant for water treatment were investigated at optimum condition. The experiment was conducted in two stages, the first method of was employed to determine which of the best particle sizes and amount of Moringa oleifera seeds powder (MOSP) for water treatment. It was observed that the 2 mm particle size performed better in terms of turbidity removal efficiency 4.98NTU, with 0.1 g. Furthermore, the second method MOSP was placed in extraction thimble to remove the oil from the seeds and produced MOCR used as bio- coagulant in water treatment. Response surface methodology was applied to determine the parametric effects of mixing speed, time and dosage on the residual turbidity. The three independent factors, such as Low speed, Low speed time and dosage were optimized using the Response Surface Methodology (RSM) for optimal water turbidity removal. The results obtained from experimental design demonstrated the optimum condition at low speed, low speed time and dosage as 40 rpm, 60 min, and 0.75 mg/L, respectively. Under this condition the predicted (theoretical) residual turbidity was 4.73 NTU. The result of the ANOVA for the optimization of the residual turbidity showed that the quadratic model was significant at 95% confidence level (p<0.05). The difference between the theoretical and experimental turbidity showed that no significant variation with a percentage error value of 1.6913 %. The quality of the treated water was determined at optimum condition using qualitative tests. The result of the water quality determination revealed that turbidity, conductivity, TDS, COD and BOD with corresponding percentage changes of 99 %, 73 %, 50 %, 75 % and 28 %, respectively. Finally, the result obtained therefore showed the potential of Moringa oleifera as natural coagulants in the effective treatment of water for drinking purpose. The lower turbidity (<5 NTU) achieved from this study confirmed the potential of this important eco-friendly natural product for the treatment of water.